The Role of Vitamin D in Inflammatory Bowel Disease: Clinical Relevance and Therapeutic Potential - Drużdżel, Anna; Pawelec, Natalia; Mazur, Weronika; Krzyżanowska, Marta; Curzytek, Kacper; Parfienowicz, Zuzanna (Quality in Sport, 2026)
Background: Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is characterized by chronic relapsing inflammation of the gastrointestinal tract. Increasing evidence suggests that vitamin D plays an important role in immune regulation and intestinal barrier integrity. Aim: The aim of this review was to evaluate the clinical relevance of serum vitamin D levels in patients with inflammatory bowel disease and to assess the potential role of vitamin D supplementation. Material and methods: A narrative review of current literature concerning vitamin D and IBD was conducted using clinical studies, systematic reviews, meta-analyses, and experimental studies retrieved from databases including PubMed and Scopus. Results: Vitamin D deficiency is highly prevalent among patients with IBD and has been associated with increased disease activity, higher inflammatory burden, greater risk of relapse and poorer quality of life. Low serum 25(OH)D levels correlate with inflammatory markers such as C-reactive protein and fecal calprotectin. Experimental and clinical studies suggest that vitamin D influences intestinal inflammation through modulation of immune responses, maintenance of epithelial barrier function, and regulation of gut microbiota. Available evidence indicates that vitamin D supplementation may improve selected clinical outcomes, particularly in patients with Crohn’s disease in remission, although current data remain heterogeneous. Conclusions: Vitamin D appears to be a clinically relevant and modifiable factor in IBD management. Routine assessment and correction of vitamin D deficiency may represent a useful adjunct to standard therapy; however, further randomized controlled trials are required to establish optimal supplementation strategies.